ILLOCUTIONARY SPEECH ACTS IN THE DRAMA SCRIPT "FRIENDSHIP" BY TOIF MALIKI - Trisna Rahmania (MEMACE: Jurnal Linguistik, Pendidikan Bahasa Indonesia, dan Asing, 2024)
The aim of this research is to determine the form of speech acts and types of illocutionary speech acts, as well as their frequency in conversations or dialogues in the drama script "Persahabatan" by Toif Maliki. This research is a qualitative descriptive research with pragmatic methods used as an analytical tool. The data source was obtained from all the dialogue or conversations of the characters contained in the drama script "Persahabatan" by Toif Malik which is closely related to everyday conversations such as those that occur in society. The research steps carried out start from the planning stage, data collection, data analysis, interpretation, and up to the preparation of a report on the findings. Based on the results of the research conducted, information was obtained that the forms of speech acts contained in the conversation or dialogue of the drama script "Persahabatan" by Toif Malik are declarative, imperative and interrogative. The types of speech acts found were directive, assertive, expressive, declarative and commissive.